The Effect of Service Quality, Customer Experience, and Customer Satisfaction on Buyback Intention at FEBI Mart Universitas Muhammadiyah Purwokerto - Akram, An Nafi Yassar Atha Al; Widayaningtyas, Dian; Hidayah, Arini; Endratno, Hermin (International Journal of Business and Applied Economics, 2025)
The purpose of this study was to determine the effect of Service Quality, Customer Experience, and Customer Satisfaction on Repurchase Intention. The study was conducted at FEBI Mart which is an entrepreneurship laboratory under the Faculty of Economics and Business, Muhammadiyah University of Purwokerto. The population in this study were 1684 active FEB students. With the number of samples selected by the researcher as many as 100 respondents, this study was quantitative. The data collection technique used the Slovin formula with an error of 10%. The data collection technique used a questionnaire with a measurement scale of the instrument using the SPSS Version 26 linear scale. The results showed that Service Quality, Customer Experience, and Customer Satisfaction had a positive effect on Repurchase Intention. The higher the quality of service provided, the higher the customer satisfaction will be. Customers who feel satisfied are more likely to be more loyal and have the intention to buy back.